2017
DOI: 10.1093/ajh/hpx017
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control During Chronic Kidney Disease Progression

Abstract: The proportion of CKD patients with poorly controlled hypertension significantly increased as CKD progressed, mainly associated with the increase in pulse pressure. However, future investigation for causal relationship between poorly controlled hypertension and its related factors is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…One-third of the patients were diagnosed with CKD stage 5. It is more difficult for patients in the late stage of CKD to control their BP [16,17]. Moreover, many of these cases had diabetes and CVD as comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One-third of the patients were diagnosed with CKD stage 5. It is more difficult for patients in the late stage of CKD to control their BP [16,17]. Moreover, many of these cases had diabetes and CVD as comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, physiological factors, such as age, stage of CKD, diabetes mellitus and cardiovascular diseases (CVDs) have been found to be inconsistent in prior studies. Older age [16], a higher stage of CKD [17], having diabetes [9] and CVD [17] have been identified as factors that are associated with uncontrolled BP. On the other hand, some studies found no association between these factors with uncontrolled BP [6,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Established risk factors such as hypertension probably explain much of the increased cardiovascular risk in CKD. Although hypertension is associated with renal dysfunction (Rao et al, 2008), more rapid progression of CKD and the development of various cardiovascular comorbidities (Go et al, 2004;Botdorf et al, 2011;Segura & Ruilope, 2011), it is common that blood pressure (BP) is inadequately controlled in CKD patients (Peralta et al, 2005;Lee et al, 2017). Non-traditional risk factors, such as inflammation and disruptions in mineral metabolism, have also been shown to play a role in the increased cardiovascular risks in CKD (Chue et al, 2010;Chue et al, 2012;Major et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported poor BP control in CKD with an apparent 2-fold variability across countries. The prevalence of uncontrolled hypertension above 140/90 mm Hg in individuals with CKD ranges from near 35% in South Korea 17 and the United States 18,19 to more than 70% in Turkey; 20 that of BP above 130/80 mm Hg varies from 55% to 65% in the United States, 18,19 65% in the UK, 21 75% in Germany, 22 80% in Japan, 23 and close to 90% in China. 24,25 Some sources of these variations among different populations may include CKD severity, prevalence of risk factors, and patterns of antihypertensive treatment.…”
mentioning
confidence: 99%